College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.7 - Rational Expressions - R.7 Assess Your Understanding - Page 71: 52


$-\displaystyle \frac{2}{(x-1)(x+1)}$

Work Step by Step

$\displaystyle \frac{2x-3}{x-1}-\frac{2x+1}{x+1}=... \quad LCD=(x-1)(x+1)$ $=\displaystyle \frac{(2x-3)(x+1)-(2x+1)(x-1)}{(x-1)(x+1)}$ $=\displaystyle \frac{(2x^{2}+2x-3x-3)-(2x^{2}-2x+x-1)}{(x-1)(x+1)}$ $=\displaystyle \frac{2x^{2}+2x-3x-3-2x^{2}+2x-x+1}{(x-1)(x+1)}$ $=\displaystyle \frac{-2}{(x-1)(x+1)}$ $=-\displaystyle \frac{2}{(x-1)(x+1)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.